Determinants of recycling intention among university students in Malaysia - Loke, Wye Meign (2014)
Malaysia biggest environmental problem is the waste management with increasing waste generation rate every year in response to Malaysia’s rapid development and low recycling rate. However, recent concerns focus on universities as it mirrors the national household waste statistics especially those provide residential accommodations operating similarly to small cities. Therefore, the understanding of university students’ recycling intention was the key to improve the recycling rate and the environment of Malaysia to be considered as environmentally responsible institutions. The present study aims to identify the unique predictors from the expanded Theory of Planned Behavior (TPB) variables (recycling attitude, subjective norm, perceived behavioral control and past recycling behavior) on recycling intentions among university students. The present study employed a quantitative research approach and correlational research design. A total of 498 Malaysian university students who live in the residential colleges provided in University of Putra Malaysia (UPM) with average age of 22 years old recruited as respondents through cluster sampling technique. The instrument used in the present study was from established measures with acceptable reliabilities for assessing the expanded TPB variables. Moreover, the data of the present study was analyzed with descriptive, bivariate and multivariate analyses. The result of descriptive analysis indicated university students have a moderate level of recycling attitude, subjective norms, perceived behavioral control, past recycling behavior and recycling intention. Then, results of bivariate findings in which the t-test analysis revealed there was a significant gender difference in recycling intention. In addition, Pearson’s correlation analysis showed all the expanded TPB variables were significantly positively related to recycling intention. Next, result of multiple regression analysis indicated all four predictors explained 22.9% of the variance in explaining recycling intention. Past recycling behavior was the strongest predictor in explaining recycling intention among university students followed by subjective norm and perceived behavioral control. However, recycling attitude did not significantly predicted recycling intention. The findings of the present study emphasized the importance of expanded TPB variables on recycling intention among Malaysian university students. Hence, intervention programs on promoting recycling among university students should emphasized on expanded TPB variables.